The derivational structures in Diwan khadim Al Hajaj - Jaafar Sadiq, Researcher. Iman; Khalaf Rasn, Assist .Prof. Dr. Hadi (Basra studies journal, 2024)
This research is about derivational structures and their meanings and how they effect the text context. The research inciudes elements suchas as houns, adverbs, gerund , particible and nouns of place and time. These grammer elements are focused in derivational forms and their effects in acontext . Semantic plays great role in how to diffrenciate between each form and structure. The gerund are very diffrent from the particible form in every thing shape or form. And their effects affect both the sentence and its meaning All derivational forms are affected by what follow them andthat how meaning of apoam appearse